A Study on Contributing Factors to Body Regions’ Discomfort among Public Sector’s Employees - Wani Othman, Irma; Jupiter, Herlina; Mohd Suki, Norazah (International Journal of Psychosocial Rehabilitation, 2019)
Assessing the current ergonomic practices information that will influence employees’ body regions is the purpose of this study. A survey questionnaire was distributed to staff in public sectors in the Peninsular Malaysia. The Statistical Package for Social Science (SPSS) version 21.0 was used for data analysis. Correlations and regression analysis was used to analyze the data. The results showed significant relationship between work station, job control, job demand, physical environment, break time, social support and body regions’ discomfort. Besides that, multiple regression analysis showed that only 18.8 percent of the variance in the body regions’ discomfort has been significantly explained by two variables (human factors and work environment). Thus, another 81.2 percent of variance explained by other variables like physiological, behavioral and motivational variables that are important in explaining the body regions’ discomfort that have not been considered in this study. It is suggested for future study to survey these variables in other industries. It is very essential to build perception on the importance of ergonomics amongst the workforce in Malaysia as such for this could lead into a higher organizational productivity and efficiency.